THE INFLUENCE OF THE APPLICATION OF PAI TEACHING MATERIALS BASED ON EXPOSITORY STRATEGIES ON LEARNING OUTCOMES OF CLASS V STUDENTS OF PARANGLOE LATA STATE PRIMARY SCHOOL, GOWA DISTRICT - Wahyuni, Sri; Marjuni; Muzakkir (Primer Edukasia Journal, 2024)
The aims of this research are (1) To describe the learning outcomes of class V students before using PAI teaching materials based on expository strategies at Parangloe Lata State Elementary School, Gowa Regency. (2) To describe the learning outcomes of class V students after using PAI teaching materials based on expository strategies at SD Negeri Parangloe Lata, Gowa Regency. (3) To analyze the differences in learning outcomes of class V students before and after using PAI teaching materials based on expository strategies at Parangloe Lata State Elementary School, Gowa Regency. The type of research used in this research is quantitative with a pre-experimental design approach with a "one group pretest-posttest" design. This research shows that: (1) The learning outcomes of students before implementing PAI teaching materials based on expository strategies in the material about my dream of being a righteous child was 49.23. (2) The learning outcomes of students after implementing PAI teaching materials based on expository strategies in the material about my dream of becoming a righteous child was 75.38. (3) Based on the paired sample t-test, a significance value (2-tailed) was obtained of 0.000. The significance value obtained is smaller than ???? (0.000 < 0.05). So it can be concluded that there is a difference in the average learning outcomes before and after being taught using expository strategy-based PAI teaching materials and the average learning outcome data has increased so that the application of expository strategy-based PAI teaching materials has a positive effect on the learning outcomes of class V students. Parangloe Lata State Elementary School, Gowa Regency.